Longitudinal changes in hematocrit in hypertensive chronic kidney disease: results from the African-American Study of Kidney Disease and Hypertension (AASK) - Chen, Teresa K. (Nephrol Dial Transplant, 2015)
BACKGROUND: Anemia is common in chronic kidney disease (CKD) and associated with poor outcomes. In cross-sectional studies, lower estimated glomerular filtration rate (eGFR) has been associated with increased risk for anemia. The aim of this study was to determine how hematocrit changes as eGFR declines and what factors impact this longitudinal association. METHODS: We followed 1094 African-Americans with hypertensive nephropathy who participated in the African-American Study of Kidney Disease and Hypertension. Mixed effects models were used to determine longitudinal change in hematocrit as a function of eGFR. Interaction terms were used to assess for differential effects of age, gender, baseline eGFR, baseline proteinuria, malnutrition and inflammation on eGFR-associated declines in hematocrit. In sensitivity analyses, models were run using iGFR (by renal clearance of I(125) iothalamate) in place of eGFR. RESULTS: At baseline, mean hematocrit was 39% and 441 (40%) individuals had anemia. The longitudinal relationship between eGFR and hematocrit differed by baseline eGFR and was steeper when baseline eGFR was <45 mL/min/1.73 m(2). For example, the absolute decline in hematocrit per 10 mL/min/1.73 m(2) decline in longitudinal eGFR was −3.7, −1.3 and −0.5% for baseline eGFR values of 20, 40 and 60 mL/min/1.73 m(2), respectively (P < 0.001 comparing the longitudinal association between baseline eGFR = 40 or 60 versus baseline eGFR = 20 mL/min/1.73 m(2)). Similarly, male sex, younger age (<65 years) and higher baseline proteinuria (protein-to-creatinine ratio >0.22) were associated with greater hematocrit declines per unit decrease in longitudinal eGFR compared with female sex, older age and low baseline proteinuria, respectively (P-interaction <0.05 for each comparison). The longitudinal eGFR–hematocrit association did not differ by body mass index, serum albumin or C-reactive protein. CONCLUSIONS: Men, younger individuals and those with low baseline eGFR (<45 mL/min/1.73 m(2)) or baseline proteinuria are particularly at risk for eGFR-related declines in hematocrit.